Aplikasi Pengekstrak Gambar Ke Excel dan Uji Ektraksi dengan Kirsch Untuk Deteksi Tepi - Hasan, Yasir; Sunandar, Hery (MEANS (Media Informasi Analisa dan Sistem), 2023)
Pixel extractor application to retrieve image pixel values and save them in Excel format. Matlab is often used for pixel extraction, but the transfer process to Excel is difficult and long if the image resolution is large. The placement of pixel values in Excel is useful for knowing the process of image processing mathematical formulas. The solution of this application is that the user can select images to be processed and the pixel extraction results are stored in three separate Excel sheets, namely red (R), green (G), blue (B), and Grayscale values. Convenience This is useful for analyzing pixel data for users. In this study, the extracted pixel values were tested using the Kirsch operator for edge detection. Doing a test of one Kirsch kernel on a grayscale sheet. This application is built using the Python programming language and the PySimpleGUI library to create an easy-to-use user interface.